2021
DOI: 10.1063/5.0058127
|View full text |Cite
|
Sign up to set email alerts
|

High performance ferroelectric ZnO thin film transistor using AlOx/HfZrO/ZrOx gate insulator by spray pyrolysis

Abstract: There is increasing interest in a ferroelectric transistor, mainly using vacuum processed hafnium oxide based materials. We report in this paper a solution processed ZnO thin-film transistor (TFT) with improved ferroelectric performance in Hf0.5Zr0.5O2 (HZO) using a triple layer of ZrOx/HZO/AlOx by spray pyrolysis. The performance enhancement is due to the difference in thermal expansion coefficient between the bottom/top dielectric and HZO layers. Grazing incident x-ray diffraction, current–voltage, capacitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The ferroelectric properties of ZAO films are analyzed from the MFM capacitor and FE-TFT device structures on the glass substrate. First, a 80/15 nm Molybdenum (Mo)/Indium Zinc Oxide (IZO) stack was deposited by sputtering, followed by patterning and wet etching to form the bottom electrode or gate electrode [18] . Subsequently, a 40 nm ZAO film was deposited using spray pyrolysis at 360 °C, and annealed for 1 h in an air furnace.…”
Section: Methodsmentioning
confidence: 99%
“…The ferroelectric properties of ZAO films are analyzed from the MFM capacitor and FE-TFT device structures on the glass substrate. First, a 80/15 nm Molybdenum (Mo)/Indium Zinc Oxide (IZO) stack was deposited by sputtering, followed by patterning and wet etching to form the bottom electrode or gate electrode [18] . Subsequently, a 40 nm ZAO film was deposited using spray pyrolysis at 360 °C, and annealed for 1 h in an air furnace.…”
Section: Methodsmentioning
confidence: 99%
“…On a different note, oxide semiconductor (OS) materials are also considered for future optoelectronics applications due to their high electron mobility, stability, and optoelectronics properties. [22,23] A number of devices have been fabricated using OSs, including zinc oxide (ZnO), indium oxide (InO x ), zinc tin oxide/ZnSnO x (ZTO), gallium zinc oxide/GaZnO x (GZO), indium zinc tin oxide/InZnSnO x (IZTO), indium gallium zinc oxide/InGaZnO x (IGZO), and indium zinc oxide/InZnO x (IZO) thin-film transistors (TFTs). [24][25][26] However the majority of these reports use vacuum deposition techniques to fabricate devices.…”
Section: Introductionmentioning
confidence: 99%
“…11,12) It has been reported that the polarization of a ferroelectric-gate insulator can be employed in oxide-channel-based FeFETs. [11][12][13][14][15][16][17][18][19][20][21] Such FETs are non-volatile and have superior transparency, making them attractive for application to transparent devices.…”
Section: Introductionmentioning
confidence: 99%